2020
DOI: 10.2478/jtim-2020-0039
|View full text |Cite
|
Sign up to set email alerts
|

Delays and gaps in progressing through the hepatitis C virus cascade of care: An underserved safety-net hospital experience

Abstract: Background and ObjectiveWhile highly effective hepatitis C virus (HCV) therapies exist, gaps in the cascade of care remain. Disparities in the HCV cascade are prominent among underserved safety-net populations. We aim to evaluate the HCV cascade among an urban safety-net cohort of HCV patients.MethodsWe retrospectively evaluated adults with chronic HCV to determine rates of linkage to care (LTC), retention to care, and receiving HCV treatment from 2002 to 2018. Comparisons between groups utilized Chi-square te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…PTMs are important components regulating microbial resistance and immunity. [29,30] New emerging evidences support that PTMs serve as interfaces between viruses, restriction factors, and cellular defense mechanisms, providing potential drug targets for future immunoregulatory therapy. [31] Many restriction factors of viruses, such as IFITM3/2, APOBEC, and SAMHD1, can be subjected to phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…PTMs are important components regulating microbial resistance and immunity. [29,30] New emerging evidences support that PTMs serve as interfaces between viruses, restriction factors, and cellular defense mechanisms, providing potential drug targets for future immunoregulatory therapy. [31] Many restriction factors of viruses, such as IFITM3/2, APOBEC, and SAMHD1, can be subjected to phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…The liver injury was relieved after prednisone treatment, and the subsequent use of Nivolumab was not affected (Alkrekshi and Tamaskar, 2021). Therefore, in patients with chemotherapy and immunotherapy, attention should be paid to the reexamination of HBV-DNA and HCV-RNA when liver injury occurs (Gomes et al, 2020). It has been reported that patients with PSC tried antivascular therapy (Jin and Yang, 2020;Kong et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Downstream from screening, follow-up testing and linkage to care for viral hepatitis has been relatively poor amongst safety-net populations. In a retrospective analysis of 600 safety-net patients with chronic HCV between 2002 and 2018, only 57.7% were seen by HCV specialists within a year of diagnosis, though the vast majority (91.6%) were followedup after the initial visit [45]. In terms of follow-up laboratory testing, data from a San Francisco safety-net system found that 22.9% of HCV antibody-positive patients did not receive further testing for HCV RNA [46].…”
Section: Screening and Follow-up Of Chronic Viral Hepatitismentioning
confidence: 99%
“…Fortunately, treatment for viral hepatitis is highly effective. Across multiple US SNHs, real-world studies report high sustained virologic response (SVR) rates for directacting anti-HCV (DAA) treatment in underserved populations with significant barriers to healthcare [45,46,[49][50][51][52]. Antiviral treatment for chronic HBV in safety-net settings has also been associated with a reduced risk of cirrhosis as well as morbidity and mortality [53].…”
Section: Screening and Follow-up Of Chronic Viral Hepatitismentioning
confidence: 99%
See 1 more Smart Citation